The effects of backward vs. forward running training on measures of physical fitness in young female handball players - Sammoud, Senda; Bouguezzi, Raja; Uthoff, Aaron; Ramirez-Campillo, Rodrigo; Moran, Jason; Negra, Yassine; Hachana, Younes; Chaabene, Helmi (Frontiers in Sports and Active Living, 2023)
Introduction This study examined the effects of an 8-week backward running (BR) vs. forward running (FR) training programmes on measures of physical fitness in young female handball players. Methods Twenty-nine players participated in this study. Participants were randomly assigned to a FR training group, BR training group, and a control group. Results and discussion Within-group analysis indicated significant, small-to-large improvements in all performance tests (effect size [g] = 0.36 to 1.80), except 5-m forward sprint-time in the BR group and 5- and 10-m forward sprint-time in the FR group. However, the CG significantly decreased forward sprint performance over 10-m and 20-m (g = 0.28 to 0.50) with no changes in the other fitness parameters. No significant differences in the amount of change scores between the BR and FR groups were noted. Both training interventions have led to similar improvements in measures of muscle power, change of direction (CoD) speed, sprint speed either forward or backward, and repeated sprint ability (RSA) in young female handball players, though BR training may have a small advantage over FR training for 10-m forward sprint time and CoD speed, while FR training may provide small improvements over BR training for RSAbest. Practitioners are advised to consider either FR or BR training to improve various measures of physical fitness in young female handball players.